A STUDY OF TEACHERS AND STUDENTS’ CODE SWITCHING IN EFL CLASSROOMS SETTING - Muslim, Muslim; Sukiyah, H; Rahman, Arif (IKIP Mataram, 2018)
This study aims to investigates a phenomenon of bilingualism in which the use of Target language (English) is switched to target Indonesia, known as code switching (CS). More specifically, the study focuses on the types of CS and the functions of CS in EFL classrooms setting. The data were obtained from classroom observations through audio recording and field notes from two different English classes. The finding reveals that both the teachers and the students employed three types of CS: inter-sentential, tag-switching, and inter-sentential switching in different contexts. Furthermore, the different frequency of CS functions employed by teachers and students? occurs both in two classes for two reasons: for social and pedagogical functions. Socially, CS in this study served as (1) conveying teacher?s admonition, (2) requesting for help, (3) helping other students, (4) commenting on the students? unsatisfactory answers, and (5) building unofficial interaction among the students. Pedagogically, CS served to (1) explain or repeat ununderstandable utterances which has been said previously in order to help students understand it, (2) check the students? understanding to the new words or expression introduced in the lesson, (3) translate sentence when students learn about grammatical features (4) repair self mistakes, (5) clarify teachers? misunderstanding, and (6) initiate a question.